If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x(-6)=6
We move all terms to the left:
-2x(-6)-(6)=0
We multiply parentheses
12x-6=0
We move all terms containing x to the left, all other terms to the right
12x=6
x=6/12
x=1/2
| 25x^2-13=36 | | 4*7+x=76 | | 30=h | | 270+x=493 | | 3i+6=7(i-2) | | 6x+3x+5x+4x=360 | | 7x–2=10+5x | | 5|x+2|=35 | | 270+x=70 | | 13x+-64=180 | | 6^x-16=200 | | 5x-2(-8x)=17 | | (n-5)(n-6)(n-7)=360 | | 2*8+12*4=14+10x | | 45/5+9x=18 | | 3i+6=7(1-2) | | 22-3x=x+6 | | 18+7-x=12-112 | | 900x=1800 | | 101+58+58=x | | 9.t=81 | | 101-58=x | | 99/9*2=27x | | 9k+21=-33 | | 101+58=x | | (4x+16)+(7x-1)=180 | | 4x+3=15–2x | | 3r+2–r=-4 | | (0.5)^3x+2=8^(5x-4) | | –8−3n=10−5n | | (2x-39)°(3x+14)= | | 2x+12=88 |